Utilizing Indonesian Metropop Novels as Material and Media in Sosiology of Literature Learning - Zulfadhli, Zulfadhli; Hasanuddin WS; Ramadhan, Syahrul (International Journal of Language Pedagogy, 2023)
This study aims to explain the use of Indonesian metropop novels as material and media in teaching the sociology of literature in universities. The sociology of literature course aims to provide students with an understanding of the relationship between literary works and various social phenomena that occur in society. Through this course, students gain knowledge about the basic concepts of the theory of sociology of literature and various forms of research using the theory of sociology of literature. This type of research is qualitative research using descriptive methods. The results of the study show that Indonesian metropop novels describe a socio-cultural phenomenon in society, especially the lifestyle and culture of urban communities who live and live in big cities which are shown through story characters. Thus, Indonesian metropop novels can be used as material and media sociology of literature learning.